ANALISIS TEOLOGIS TERHADAP KONSEP KEPEMIMPINAN KRISTIANI DALAM SURAT 1 TIMOTIUS DAN PENERAPANNYA DALAM KONTEKS MODERASI BERAGAMA - Windi Windi; Verayanti Randa, Fredereta Natali, Ayulia Sriningsi, Resal Patabang (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study aims to conduct a theological analysis of the concept of Christian leadership found in the First Epistle to Timothy, and to consider its application in the context of religious moderation. The First Epistle to Timothy serves as a pivotal source in understanding the principles of Christian leadership in the early Church. Through a literature review approach, we engage in exegetical analysis of this biblical text, examining its historical context, language, and underlying theology. Furthermore, this research scrutinizes the implications and applications of Christian leadership concepts within the increasingly relevant context of religious moderation in contemporary times. By leveraging hermeneutical studies and reviewing current literature, we identify potential challenges and unique opportunities arising in the context of religious moderation, as well as how the concept of Christian leadership can provide a solid foundation for managing diverse beliefs. The results of this study are anticipated to offer deep insights or knowledge on how the principles of Christian leadership found in the First Epistle to Timothy can be translated and applied in the context of religious moderation. The practical implications of these findings can serve as valuable guidance for Christian leaders in guiding faith communities amidst a plurality of beliefs. In conclusion, this research not only provides a profound understanding of Christian leadership concepts but also offers a fresh perspective on their relevance in facing complex challenges in contemporary times.